(untitled) - Woloch, Nancy (New York, 1994)
The book is an introduction to the history of American women, based primarily on recent scholarship. It focuses on women's experience in family life, economic life, and public life, with attention to the pervasive impact of class and race
Keywords: Women; History; United states